Endodontic mishaps during root canal treatment performed by undergraduate dental students: An observational study. Issue 47 (24th November 2021) - Alghamdi, Nuha S.; Algarni, Youssef A.; Ain, Tasneem Sakinatul; Alfaifi, Haifa M.; AlQarni, Alaa A.; Mashyakhi, Jamilah Q.; Alasmari, Sara E.; Alshahrani, Muhanned M.
Abstract : Abstract: Endodontic mishaps during root canal treatment (RCT) are considered to be one of the most commonly encountered errors, which affect the quality of treatment and may have dangerous health implications for patients. The present study was conducted to assess the frequency and types of endodontic mishaps in root canal-treated teeth performed by undergraduate dental students. A total 404 endodontically treated teeth were performed by undergraduate dental students of King Khalid University College of Dentistry, Abha, Kingdom of Saudi Arabia. The radiographs of the endodontically treated teeth were studied for a period of 6 months, and the related demographic data were collected from patient files. The most commonly identified mishaps were related to obturation, where the maximum number of cases (68.1%) had under-obturated root canals. More endodontic mishaps were performed by students in level 9 education. The upper left 2nd molar teeth had a higher frequency of mishaps, and molars were found to have more access-related mishaps. Lastly, access-related and instrument-related mishaps had a low frequency of occurrence. The majority of endodontic mishaps found in the study sample were related to root canal obturation. The undergraduate students at level 9 were less proficient in conducting RCTs with many endodontic mishaps when compared to the cases performed by students at higher levels. The study suggests relevant guidance for dental students while performing RCTs, especially during obturation of the root canals.